PERANCANGAN SMART MOBILITY RUTE DAN KEMACETAN LALU LINTAS BATAM - Sherly Agustini; Aysha Ayshia Rey; Harkam Tujantri (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: Traffic congestion in Batam City has become one of the major issues affecting community mobility due to the increasing number of vehicles and the limited availability of road condition information. This study aims to design a Smart Mobility system capable of providing traffic congestion information and recommending more efficient travel routes. The research employed the Waterfall method, which consists of the stages of requirement analysis, system design, implementation, testing, and maintenance. Data were collected through observation, literature review, and secondary data, including road network data, traffic congestion data, route data, estimated travel time, and user input data. The result of this study is a Smart Mobility system prototype featuring user login, dashboard, route search, traffic information, and route recommendation functions. System testing using the Black Box Testing method demonstrated that all main features functioned according to the specified system requirements. Therefore, the proposed system is expected to serve as a foundation for the development of intelligent transportation systems in Batam City and to assist the public in obtaining more effective and efficient travel information. Keywords: Smart Mobility; Traffic Congestion; Route Recommendation; Waterfall; Black Box Testing; Batam City.   Abstrak: Kemacetan lalu lintas di Kota Batam menjadi salah satu permasalahan yang memengaruhi mobilitas masyarakat akibat meningkatnya volume kendaraan dan keterbatasan informasi mengenai kondisi jalan. Penelitian ini bertujuan merancang sistem Smart Mobility yang mampu memberikan informasi kondisi kemacetan serta rekomendasi rute perjalanan yang lebih efisien. Metode penelitian yang digunakan adalah metode Waterfall dengan tahapan analisis kebutuhan, perancangan sistem, implementasi, pengujian, dan pemeliharaan. Pengumpulan data dilakukan melalui observasi, studi pustaka, dan penggunaan data sekunder berupa data jalan, data kemacetan, data rute, estimasi waktu tempuh, serta data masukan pengguna. Hasil penelitian berupa prototype sistem Smart Mobility yang memiliki fitur login, dashboard, pencarian rute, informasi kemacetan, dan rekomendasi rute perjalanan. Pengujian menggunakan metode Black Box Testing menunjukkan bahwa seluruh fitur utama telah berfungsi sesuai dengan kebutuhan yang dirancang. Dengan demikian, sistem yang dirancang diharapkan dapat menjadi dasar pengembangan sistem transportasi cerdas di Kota Batam serta membantu masyarakat memperoleh informasi perjalanan yang lebih efektif dan efisien. Kata kunci: Smart Mobility; Kemacetan Lalu Lintas; Rekomendasi Rute; Waterfall; Black Box Testing; Kota Batam.